Unusual Presentation of Wilms' Tumor as Umbilical Granuloma - Hegde, Shalini Gajanan; Menon, Prema; Narasimha Rao, Katragadda Lakshmi; Nada, Ritambhra (Indian Journal of Medical and Paediatric Oncology, 2018)
We report an unusual presentation of a Wilms' tumor in an 8-month-old child, incidentally detected by ultrasonography for an umbilical granuloma. A patent vitellointestinal duct anomaly required surgical excision in the same sitting as the nephroureterectomy. The case is reported for the unusual coexistence and the management implications.
Keywords: Incidental diagnosis; umbilical granuloma; vitellointestinal duct anomaly; Wilms' tumor